Comparison of Mortality between Intravenous Albumin and No Intravenous Albumin in Sepsis Patients with Hypoalbuminemia Conditions and Factors that Influence the Mortality of Sepsis Patients - Marzuki, Mochammad Jalalul; Supriono, Supriono; Pratomo, Bogi; Mustika, Syifa (UI Scholars Hub, 2019)
Introduction. Hypoalbuminemia is a strong predictor of mortality in nonoperative and operative patients. Albumin plays a role in maintaining oncotic pressure in critical conditions such as sepsis. The administration of exogenous Human Serum Albumin (HSA) in sepsis with hypoalbuminemia conditions is still controversial with varying outcomes.This study aimed to know the mortality ratio between intravenous albumin administration and no intravenous albumin administration in sepsis patients with hypoalbuminemia conditions and also to know the factors that influence the mortality of sepsis patients. Methods. An observational study with a prospective approach involving 75 research subjects aged >18 years with sepsis accompanied by hypoalbuminemia (<2.5 g/dL) treated in the high care unit of RSUD dr. Saiful Anwar Malang during the period 1 September 2018-31 August 2019. Subjects were divided into two groups namely albumin and nonalbumin groups. Both groups were followed during hospitalization until they discharged or died. Differences in mortality between the two groups were analyzed by chi square bivariate test. The most influential factors on mortality were analyzed by multivariate binary logistic regression tests. Results. There were 39 people (52%) from the albumin group and 36 people (48%) from the non-albumin group. Difference in mortality between albumin and nonalbumin groups 25 (64.1%) vs 16 (44.4%) with OR 2, p=0.138 means there was no statistically significant difference. Factors that influence mortality included: SOFA score (OR 34.27, p <0.001), MAP value (OR 8, p<0.001), septic shock (OR 4.31, p=0.03), diabetes mellitus (OR 0.28, p=0.009), respiratory failure (OR 8.02, p <0.001), decreased of consciousness (OR 64.75, p <0.001), cardiovascular failure (OR 6, p <0.001), hematological failure (OR 3.05, p=0.027). The most dominant factor affecting mortality in sepsis patients is decreased of consciousness (OR 2.67, p=0.001). Conclusion. The administration of albumin transfusion did not make a significant difference in the incidence of mortality in sepsis patients with hypoalbuminemia. The most influential factor on mortality of sepsis patients is decreased of consciousness.